(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Jobs are not manna falling from the heaven. They are created by utilising natural resources and human resources. Utilisation of natural resources and human resources requires manufactured resources what may be called capital (man-made goods). India is endowed with natural resources and good size of population, still India is suffering from unemployment. The problem lies not in natural resources but in the composition of population or demography. Unemployment in India is totally different from that of developed countries. There are three main types of unemployment, distinguished according to causes, are (i) unemployment arising from deficiency in aggregate demand (ii) unemployment arising from shortage of capital equipment or other complementary resources and (iii) frictional unemployment. The first type is mainly cyclical in character and has been recurring in all advanced countries from time to time. The second is found mainly in under-developed countries, like India, while the third may occur in any type of economy. The nature of unemployment exist in India can be lowered by developing human resources through education, training, and skilled development programmes and by improving over natural resources (called additional capital), such as irrigation ditches in farming communities or access roads in towns based on mining or forestry. To assess the magnitude of the problem in quantitative terms with the existing data on the subject is an almost impossible task. The paper focuses on the causes and the nature of unemployment in India and how it can be done away with through development of economic and social infrastructure.